Development of Hepatocellular Carcinoma in a Patient with Chronic Hepatitis C 21 Years after Achieving a Sustained Virological Response to Interferon Therapy - Tasuku Hara; Tomoya Ohara; Masashi Taniguchi; Toshiaki Sakai; Kohei Oka; Naoto Iwai; Toshifumi Tsuji; Takashi Okuda; Toshiyuki Komaki; Junichi Sakagami; Keizo Kagawa (Case Reports in Hepatology)
A 77-year-old man with chronic hepatitis C (CH-C) infection, who achieved a sustained virological response (SVR) to interferon (IFN) therapy, was followed up regularly. Before IFN therapy, he did not have metabolic diseases, and the histological diagnosis of his chronic hepatitis was stage-3 fibrosis. After achieving SVR, the fibrosis-4 (FIB-4) index level dropped once but gradually increased. 21 years after SVR, hepatocellular carcinoma (HCC) was diagnosed by dynamic computed tomography. The HCC was 12 mm in diameter. The HCC was treated with radiofrequency ablation. CH-C patients with advanced fibrosis require long-term follow-up, even after achieving SVR.